The role of mass media and merchandising in the etiology of unplanned purchases - Zawadzki, Rafał (Current Problems of Psychiatry, 2011)
Consumeric mentality gives rise to a growing number of risks enslaving an individual. Nowadays people are continually bombarded by the information coming from various sources. Advertising is present almost everywhere and, as a result of using various persuasion methods, affects human psyche. Hundreds of thousands of radio and television programmes and newspaper articles impose upon their addresses their way of interpreting the reality often in a camouflaged way that distorts its true image. Mass media undoubtedly promote material values as the ones that can ensure happiness and help the individual live in harmony in the state of homeostasis. However, research conducted so far seems to contradict the advertising slogans by proving that there is a lack of positive correlation between the amount of possessions and happiness as well as life satisfaction. As it is pointed out in the article, the media related factors inducing unplanned purchases, allow us to formulate some conclusions. The effect of mass media cannot be limited only to persuasion, but it is meant to manipulate the addressee of the message. We can see more and more of actions targeted at creating something that can be defined as “consumption mentality”, which can provide the basis for manipulating customers in an easier way. It is accompanied by the development of the new media, whose impact is much greater. The media influence does not seem to determine uncontrolled consumer behaviour, however it adds undoubtedly to revealing incorrect situations in this respect that can potentially exist. The shopping situation provides a number of stimuli to the person being already in the shop, or the one who intends to enter it. It is becoming more and more common that the situation that a customer encounters in the shop is not a pure accident, it is not just a fad, but the consequence of carefully designed and planned marketing strategies. As the analysis of the literature on merchandising shows, the buying situation has become a consumption plane, which is being manipulated in order to increase sales. The techniques used by merchandising specialists increase undoubtedly the sales volumes as well as the unplanned purchase ratio, however, they cannot be considered the only factor that could contribute to generating shopaholics